Human posture recognition : methodology and implementation - Htike, Kyaw Kyaw; Khalifa, Othman Omran; Lai, Weng Kin (IIUM Press, 2011)
Human Posture Recognition is a key component of many application-oriented computer vision systems, for instance in automated visual surveillance, automotive safety, computer interaction and multimedia processing. Human tracking is an important part at 3 automated video surveillance system. It is used to track any previously detected human to the mapping or prediction purpose or simply for behavioural analysis. High detection r and low false alarm rates are essential for achieving robustness in higher level vision tas such as tracking or activity recognition